Political pr in the field of international relations - A. K. Botasheva; I. A. Gereikhanova; V. N. Panin (Современная наука и инновации, 2022)
The increased influence of information technology has led to the fact that the issue of building not only effective, but also systemic communications has become urgent, as far as the order of international relations needs more predictable, more open interactions of an interstate nature, including in the field of political PR.